The difference in tensile bond strength of an adhesive cement resin to an etched and perforated resin-bonded bridges: Perbedaan tensile bond strength dari resin semen adesif dengan gigi tiruan jembatan etsa dan perforansi - Silvia Naliani; Deddy Firman; Aprillia Adenan (Makassar Dental Journal PDGI Makassar, 2022)
Several improvements to the metal cast framework have been suggested since resin-bonded fixed partial dentures was introdu-ced. Essentially, there are twotypes of retainer designs based on retention namely macromechanical retention with a perforated retainer commonly referred to as Rochette bridge and micromechanical retention derived from the etched metal cast retainer called as Maryland bridge. This study is aimed to compare the tensile bond strength of anadhesive cement resin to an etch and perforated resin-bonded bridge. Using experimental laboratory design, the sample tested consisted of 10 plates Ni-Cr alloy,13 mm in diameter and 1 mm in thickness were divided into two treatment groups; five plates were perforated, and five plates were etched using Met-Etch Gel. Tensile strength was determined using an Ametek Llyod Instrument. The result showed that the strength of resin adhesive cement on the metal surface of alloyNi-Cr used etch higher than perforated. Statistical analysis used student t-test recorded t-test 2.75 and p-value 0.0125, so it said significant differences becausep-value was smaller than 0.05. This study showed that etch cast metal retainers were more retentive than perforated design.